Liquid-liquid phase separation heat transfer in advanced micro structure. (December 2018) - Xing, Wei; Plawsky, Joel; Woodcock, Corey; Yu, Xiangfei; Ullmann, Amos; Brauner, Neima; Peles, Yoav
Highlights: An experimental study of using Triethylamine (TEA)/water solution along with advanced micro structure is presented. Such mixture and structure combination enables heat removal of at least 500 W/cm 2 at mass flux of 600 kg/m 2 s, while the heated surface temperature is below 80 °C. Various geometrical structures and flow conditions are tested to provide a complete understanding of the heat transfer process. The results are useful to help design micro heat sink with advanced structures. Customer-defined dimensionless parameters are used to characterize the phase separating convection heat transfer process. Computational fluid dynamics (CFD) tool is used to provide additional physical insights. Abstract: An experimental heat transfer study using triethylamine (TEA)-water solution as a coolant in a Piranha Pin Fin (PPF) structure is reported here. The triethylamine-water solution undergoes phase separation when heated to a temperature over 18.2 °C at a TEA mass fraction of 32.1% (i.e., critical composition). This separation process was proven to enhance heat transfer in the plain channel geometry. With the aid of the PPF structure, the TEA-water solution was able to dissipate a heat flux of up to 500 W/cm 2 at a mass flux of 600 kg/m 2 s and to keep the surface temperature below 80 °C. The phase separation of a TEA-water mixture in the PPF structure yields about 1.8 times greater heat transfer coefficient compared to a corresponding homogeneous mixture flow. Flow boiling was achieved during experiments when the heat flux exceeded 600 W/cm 2 . The effects of different configurations of PPF were also studied, and it is shown that the PPF configuration with fewer and smaller fins provides the best performance enhancement over water flow at the same mass flux. Two flow conditions, channel flow and extraction flow, were examined. The TEA-rich phase was extracted during the extraction flow experiment and the remaining water-rich phase results in favorable thermal transport performance. A string-shaped flow pattern is observed due to both shear force and the flow disturbance provided by the PPFs. The system exhibits reduced pressure drop as the fluid viscosities decrease after phase separation.